An assessment of Putative Sexually Antagonistic Traits in a Freshwater Amphipod Species. (21st April 2015) - Cothran, Rickey D.; French, Beverly J.; Relyea, Rick A.; Ebensperger, L.
Abstract Sexual conflict can result in an 'evolutionary arms race' between males and females, with the evolution of sexual antagonistic traits used to resolve the conflict in favor of one sex over the other. We assessed the resolution of sexual conflict in a Hyalella amphipod species by manipulating putative sexually antagonistic traits in males and females and used mate‐guarding duration as our metric of conflict resolution. We discovered that large male posterior gnathopod size increased mate‐guarding duration, which suggests that it is a sexually antagonistic trait in this species. In contrast, female and male body size did not significantly affect mate‐guarding duration. Given that male posterior gnathopods show heightened condition dependence, future investigations should explore the interactive effects of sexual conflict and ecological context on trait evolution, phenotypic divergence, and speciation to elucidate the complex mechanisms involved in the evolution of biological diversity.